El Excentrico, 1971-06-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
June 5, 1971 [5 de junio de 1971]. No volume or issue number. Cover has portait photographs of five women (clockwise from top left: Ortencia Rivera, Priscilla Rivera, Terilee Lucero, Cindy Garcia, Rose Medina) for the 3rd Annual Coronation & Scholarship Dance for the New Mexico Club in Sunnyvale, California.